STUDENTS' THINKING PROCESS IN SOLVING MATHEMATICAL PROOF PROBLEM - Fauziah Hakim; Murtafiah Murtafiah (IAIN Ambon, 2020)
TThis research aimed to describe students’ thinking process in solving mathematical proof problem. The subjects in this research were Mathematics Education Study Program students in Universitas Sulawesi Barat who were taking Abstract Algebra course on academic year of 2019/2020 and were grouped into 3 proving ability categories, high, medium, and low. For each category, two subjects were chosen to be interviewed in order to obtain a description of students' thinking processes. From the results of tests and interviews, it was found that in the entry phase, high and medium category subjects were able to find the right initial verification procedure, whereas low category subjects were not yet able. In the attack phase, high category subjects were able to complete the process of proof to the final stage very systematically, medium category subjects were able to use the properties and theorems but still have difficulty achieving the right end result, while low category subjects try to use the properties and theorems but are not related to the verification process. In the review phase, high category subjects were able to explain the procedure outline again, category subjects were trying to supplement the shortcomings of the procedure, and low category subjects realized the importance of the initial proof process.